Devalued Body of The Grobogan Tayub Dancer - Aqirul Mala, Puspa (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2023)
Abstract This study aims to describe how Lasmi, a Tayub dancer Legend from Grobogan (an area near the North Kendeng Mountains) experiences others in various aspects of her life, especially when she lives in the art stage. The author uses the in-depth interview method in addition to supporting documents such as previous research, YouTube channels, news, and interviews with supporting sources by absorbing awareness of gender-based insights and feminism. The author borrows the theory of Liyan or subaltern/ the others from Gayatri Spivak and De Beauvoir which describes how women live and grow with the experience as the other group or not the main one. The research subject is Lasmi, who had her heyday in the 1980s to early 2000s. Lasmi is an example of an Indonesian postcolonial body, which means a body who does not come from a center of power, and does not come from the center of the metropolitan modern arts of its time. A body like this experiences otherness and marginalization in society and always becomes an object, especially from a male point of view or male gaze. The body of the other is always close to experiencing problems, being number two, and always being compared to others. In her life, Lasmi was experienced as the other in both public and domestic areas. Serving the public area when she was working as Waranggana Tayub was required to please many people, did not have full rights over his body, did not have enough time to rest, did not have maternity rest was adored if she was beautiful, and was bullied if she was ugly. Even so, she also experienced the others or subalterns in the domestic area. She is also a breadwinner and must also be demanded to be perfect in the house. She experienced domestic violence, was physically exhausted, and did not have full control over the money she earned. Even though she had experienced her heyday, in the era of the COVID-19 pandemic she was also included in a marginal group that was highly trained, due to the PSBB (Large-Scale Social Restrictions) so she could no longer dance and performed as she used to be. She has also suffered from an age devaluation, which has resulted in her being rarely invited for performing arts, and losing out to the young waranggana. Keywords: Gender, Feminism, Liyan, The Other, Subaltern, Kendeng, Tayub, Grobogan, COVID-19, Postcolonial Feminism